Advances in Applied Marine Sciences and Engineering - Zhao, Enjin; Mu, Lin; Qin, Hao (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In recent years, applied marine sciences and engineering has attracted worldwide attention, which includes basic theoretical research and applied research on marine hydrology, meteorology, physics and geology. Besides, new viewpoints, new developments, new theories, new methods, new applications and new experiences of investigation, research and management in the marine environment and big data, ocean and coastal engineering, marine/coastal disaster and risk assessment, river dynamics, marine ecological environment, marine instruments and equipment, etc. are also included. This Special Issue aims to address the recent advances in marine environmental information and the application of marine environmental information.